Activation of Hageman Factor (HF, Factor XII) by Sephadex-Ellagic Acid Mixtures - Ratnoff, O. D.; Saito, H. (Thrombosis and Haemostasis, 1977)
In the intrinsic pathway of clotting, PTA (Factor XI) is activated by activated HF. Whether activation of HF requires the presence of prekallikrein (Fletcher factor) and high M. W.(HMW) kininogen (Fitzgerald factor), or whether these agents act after activation of HF is disputed. Purified HF activates PTA in the absence of prekallikrein, but this may reflect molecular changes in HF during purification.Sephadex G10 or G15 was mixed with ellagic acid and freed of excess ellagic acid by washing. A mixture of normal plasma, or plasma deficient in HF, prekallikrein, HMW kininogen or PTA, and Sephadex-ellagic acid was centrifuged at 31000 xg. Each supernatant plasma except that deficient in HF shortened the abnormally long partial thromboplastin time (PTT) of HF-deficient plasma. Plasma simultaneously depleted of HMW kininogen, prekallikrein and PTA also shortened the PTT of HF-deficient plasma and of plasma depleted of HF and prekallikrein (albeit minimal clotting times were reached more slowly in the latter case) but had virtually no procoagulant effect upon the PTT of plasma depleted of HF and HMW kin inogen.Thus, exposure of HF in plasma to Sephadex-ellagic acid generated a clot-promoting form of HF in the absence of other clotting factors, but its full expression requited the presence of HMW kininogen.